The Application Analysis of Article 1365-Civil Code Towards The Responsibility of E-Commerce Platforms for Products Sale with Changed Brandings Without Permission - Monalisa, Angelia Carla; Surahmad, Surahmad (Law Development Journal, 2025)
The background of this research is based on the rapid development of e-commerce which has led to an increase in the circulation of branded products that have been altered without permission. This action has the potential to harm brand owners and create an unhealthy trading climate in the digital world. This study aims to analyze the application of Article 1365 of the Civil Code (KUHPer) to e-commerce platforms that facilitate the sale of branded products that have been altered without permission, as well as to examine the role of platforms in protecting intellectual property rights in the world of e-commerce. The method used is a normative legal approach that emphasizes the analysis of legal regulations and related literature. The results of the study indicate that e-commerce platforms can be held liable for unlawful acts related to the sale of branded products that have been altered without permission, especially if there is evidence of negligence or an active role in allowing the practice. This study also found that the protection of intellectual property rights in e-commerce still requires strengthening regulations and more effective supervision to prevent violations that are detrimental to the parties involved.